A glimpse of evil : part I of a trilogy - Podlesny, Norbert (HAF Books, 2018)
This trilogy is a collection of photographs, documents, and artifacts, showing the tragic stories of persecution and holocaust that took place before and during the greatest conflict in the human history of the Second World War